The key elements of cultural intelligence as a driver for digital leadership success - René Rüth; Torsten Netzer (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
In today's globalized economy, being successful in an industry almost necessarily implies an international approach of doing business. Restricting one's economic activities to the domestic market will ultimately lead to disadvantages in comparison to multinational companies which are able to grow rapidly in emerging markets. The digital transformation further increases the possibilities for companies that operate across national borders and has become the enabler to serve customers all around the world and increase the responsiveness of the business in all areas. At the same time this fact further increases the pressure on companies driving global hypercompetition. In order to survive in this globalized, hypercompetitive world companies need to embrace the opportunity and internationalize their business. One of the main tools for successfully operating in different business cultures is the ability to manage the workforce in an international environment. Not only the foreignness of the new markets a company is operating in but also the different cultures of the team members are challenging modern leaders. The concept of cultural intelligence (CQ) provides the toolset to manage a diverse workforce from various cultural backgrounds within one organizational framework. CQ will be explained and its importance for digital leadership will be discussed. Especially when communication across borders and interaction between members and customers from different cultural background happens in real-time it is important to understand and interpret behavior correctly and communicate or act with a high and flexible cultural awareness. This is where the paper will line out that CQ has become an important tool for leadership success in a digital world and will explain the key elements of CQ with the highest influence on leadership in this digital setting.
Keywords: 330; Cultural intelligence; Leadership; Intercultural management; Digital transformation